ANALISA FAKTOR RISIKO KOMPLIKASI GAGAL JANTUNG PADA PASIEN HIPERTENSI DI RSUD ULIN BANJARMASIN - Suryadi, Suryadi; Solikin, Solikin; Uni, Uni (STIKES Suaka Insan, 2024)
ABSTRACT Hypertension is associated with an increased risk of heart failure and can lead to various complications—multiple risk factors cause heart failure. To reduce the risk of complications, it is essential to implement preventive measures and manage hypertension through lifestyle changes and medication adherence. This study design uses a correlational approach with a cross-sectional methodology. The population consisted of all hypertension patients at Ulin General Hospital, averaging 190 individuals, and the sample, calculated using Slovin's formula, included 129 respondents selected through accidental sampling. Data analysis was conducted using the Spearman rank technique. The study results show that there were 74 male respondents (57.4%), 52 elderly respondents (40.3%), 108 respondents with light physical activity (83.7%), and 112 respondents with uncontrolled hypertension (86.8%). The factor associated with heart failure complications was hypertension, whereas factors such as gender, age, and physical activity were not related to heart failure complications. Future research should use a cohort method to obtain more precise results.